Tumbuh Kembang dan Permasalahan Kesehatan Pekerja Anak - I Ketut Labir; Ni Luh Kompyang Sulisnadewi; I Gde Widjanegara (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2017)
This study uses a quantitative method with study cross-sectional approach. The total sample of 40 people, samples taken technically in total sampling. Data were collected by questionnaires for 4 months and a variable relationship analysis performed with correlation Spearman rank test. The results showed the characteristics of respondents, found the vast majority (67.5%) of workers child-sex male and 32.5% female. Most (62.5%) working children are school-age children and 52.5% of working children are not formal schooling, the majority (67.5%) growth in child labor normal nutritional status, psychosocial development of a small portion (25%) in the category less, 52.5% of health problems is ISPA and the correlation between age, gender and psychosocial development of the respective P value equal to 0.032 less than value = 0.05 and P value of 0.044 less than value = 0:05